2010
DOI: 10.1016/j.jbusres.2009.02.009
|View full text |Cite
|
Sign up to set email alerts
|

Developing pandemic communication strategies: Preparation without panic

Abstract: Communication in the media regarding a potential avian influenza epidemic can serve to accurately and effectively inform the public OR misinform and contribute to unnecessary public panic and subsequent undesirable responses. Governments have time to develop communication strategies and specific messages that can effectively convey desired information at different stages of the anticipated pandemic. Effective social marketing incorporates the concepts of formative research, audience segmentation, and consumer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
68
1
5

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(74 citation statements)
references
References 17 publications
0
68
1
5
Order By: Relevance
“…Despite the importance of the media in providing essential information to the public, it has been suggested that different pressures and motives influence what information is transmitted (Elledge et al, 2008;Jones et al, 2010). In the present study, a majority of individuals believed media reports, but indicated that the media would sensationalize or present contradictory information.…”
Section: Discussioncontrasting
confidence: 64%
See 2 more Smart Citations
“…Despite the importance of the media in providing essential information to the public, it has been suggested that different pressures and motives influence what information is transmitted (Elledge et al, 2008;Jones et al, 2010). In the present study, a majority of individuals believed media reports, but indicated that the media would sensationalize or present contradictory information.…”
Section: Discussioncontrasting
confidence: 64%
“…Transparency about what is known, and that which is not known in relation to viral disease is critical to establish trust in government and media (Larson & Heymann, 2010), whereas distrust is increased by contradictory or missing information and by opposing opinions (Jones, Waters, Holland, Bevins, & Iverson, 2010). When a health threat, such as a novel flu strain appears, medical officials may not have all the answers to communicate to the public.…”
Section: Swine Flu (H1n1) Reached Pandemic Proportions In 2009 Yet Amentioning
confidence: 99%
See 1 more Smart Citation
“…Social marketing has existed for quite some time, and its uses continue to grow (Brennan & Binney, 2010;Creyer & Ross, 1997;Dann, 2010). When used effectively, social marketing is a powerful tool that can bring about behavioral change for the benefit of individuals, groups, and society as a whole (Jones, Waters, Holland, Bevins, & Iverson, 2010). However, as Wymer (2010) previously notes, the typical (short-lived) social marketing approach to obesity-related problems is to encourage individuals to exercise more or to eat more fruits and vegetables.…”
Section: Consumer Health and Social Marketing Initiativesmentioning
confidence: 99%
“…For instance, media reports on Avian Flu were found to both quell fears by providing accurate information, but also promoted inappropriate anxiety (Jones, Waters, Holland, Bevins, & Iverson, 2010). Individuals who tend to be wary of uncertain situations may increase or decrease the importance of reported health risks in accordance to the perceived biases they believe public health agencies hold (Fischhoff, 1995).…”
Section: Protection Motivation Theory (Pmt)mentioning
confidence: 99%